A caracterização da produção de materiais didáticoeducativos audiovisuais para educação superior a distância na UFSCar - Montanaro, Paulo Roberto (Universidade Federal de São Carlos, 2010)
This survey aims to collect data on the production of audiovisual content intended for undergraduate courses in e-learning mode. Mapped Thus, each of the elements produced, their production system and the actors who work directly or indirectly in the construction of these materials. Therefore, we attempted to trace a brief history of the development of several other audiovisual productions over the years that have passed, so that they know the way political, aesthetic and linguistic achievements they had so far. Likewise, it also draws a picture on the understanding of the system applied in the university, through the project called Universidade Aberta do Brasil, known by the acronym UAB, as well as its structure around a specific department, the Secretaria Geral de Educação a Distância, or SEaD, within the Universidade Federal de São Carlos - UFSCar - which is also critical to understand that one can macroscopically pedagogical issues, techniques and systematic material produced there. Thus, the creation of an audiovisual team within the structure of this department is essential for the project shows that the process of teaching and learning for the proposed project, since the use of multiple media is the basic assumption in this system. The evolution of team formation, their training and the duties performed by each of its elements are extremely important for understanding the intentions of undergraduate courses created and there is part of this research, as well as developments in its production process, procedures and results. That said, means the audiovisual production focused on e-learning as part of a larger system and complex content and instructional materials were defined and delimited by the collaboration between the different actors involved in the process, as well as limitations and technical characteristics of the process, production time and internal policies of the political-pedagogical project of the institution and the course as a whole.
The production of didactic and educational audio-visual e-learning material at UFSCar
Keywords: Comunicação; Comunicação audiovisual - estudo e ensino; Educação a distância; Material didático; Objeto de aprendizagem; Audiovisual educativo; Produção audiovisual; Audiovisual education; e-Learning; Audiovisual Production; Learning materials; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO